Parentsâ talk and early literacy in preschool children - Dabiri, Asma (Journal on English as a Foreign Language (JEFL), 2018)
In this research, childrenâs early understanding of the functions of print and parentsâ mediation, talk about the purpose of writing, and their elaborative reminiscing talk was investigated in Persian preschoolers. The study was a mixed-method type of research. Preschool children (seventeen girls and thirteen boys) and their mothers participated in the study. In order to obtain data, they were involved in a task game (a grocery-list task) obtained from the experts and they discussed a past event together. Analyses of the obtained data revealed that children with better notating skills had parents who provided more assistance when notating and used more elaborative talk, but did not talk more about the purpose of writing. The results suggested that in pre-school years, what parents did and said may play a role in childrenâs symbolic, numeracy, and literacy development, although it did not relate to childrenâs mastery of the conventions of print. Finding this continuity is important because it helps researchers revise and bridge theories about parenting and childrenâs early literacy and numeracy and symbolic development.